Identificación de leishmania utilizando la técnica de giemsa en pacientes atendidos en el hospital provincial, puyo durante el período de junio a noviembre del 2013 - Vallejo Lasso, María Gabriela (2013)
The leishmaniasis is a disease that appears after the inferction produced by a protozoan of the genus leishmania that parasite the cells of the reticulo-enditelial systems.Humans and animals become infected with leishmaniasis if they are bitten are by female flies of the generes Phlebotomus and Lutzomya.